Entrepreneurial Instinct of Principal to Manage Production Activities in Christian Pandhega Jaya High School - Haekase, Yongky Defridus; Fakhruddin, Fakhruddin; Yulianto, Arief (Educational Management, 2020)
Entrepreneurial instinct is one of the dimensions of entrepreneurial competence that must be possessed by the principal, by having an entrepreneurial instinct the principal can manage production/ service activities in the school as a source of learning for students. The purpose of this study is to analyze the dimensions of the principals' entrepreneurial instincts in planning, organizing, implementing and supervising school production/ service activities as a source of learning for students in Pandhega Jaya Christian High School. This research uses a qualitative approach with case study design. The purpose of this study is to analyze the principals' entrepreneurial instincts in planning, organizing, implementing and monitoring school production/ service activities as a source of learning for students. The research sample consisted of school principals, teachers and students. Data collection techniques using in-depth interviews, observation and documentation. The results showed that the principal already had an entrepreneurial instinct in managing school production/ service activities. in the case of planning, it is carried out by planning a work program of production activities together with the management team, budget planning, raw materials and tools, sources of business capital and preparing supporting facilities. In terms of organizing done by arranging human resources, infrastructure, implementation of production activities carried out in accordance with the plan that is as a source of learning for students. Supervision is carried out jointly by employees, principals and teachers to ensure that implementation is in accordance with planning. With good management of school production/ service activities, the principal has prepared learning resources for students, equipping graduates to work in the business world as well as an alternative school income in terms of funding.